A College Graduate Confesses to a Murder He Did Not Commit: A Case of a Voluntary False Confession. Issue 2 (14th March 2016) - Kavanaugh, Antoinette E.
ABSTRACT: Juries and judges are persuaded by confession evidence. Unfortunately, some of these confessions are false and result in the conviction of an innocent person. Most false confession cases involve police interrogations. On the other hand, a spontaneous or voluntary false confession involves a person confessing to a crime he or she did not commit, absent police interrogation. This case is one in which Mr. Johnson, a college graduate, confessed to a serious crime he did not commit. Although his confession was inconsistent with the facts of the crime, the police arrested Mr. Johnson. The following case study describes the forensic evaluation conducted in Mr. Johnson's case, the outcome of his case, and the impact of voluntary false confessions.